Children In The Built Environment - Yong Adilah Shamsul Haramain,; Nik Elyna Myeda,; Norhayati Mahyuddin, (2025)
“Children in the Built Environment” is a work of passion that was authored by three researchers in the field of Built Environment who are profoundly dedicated to enhancing the urban environments in Malaysia for children. Each author contributes a distinctive perspective, which is inspired by a common goal to promote child-friendly environments that facilitate the development and experiences of children in urban environments. This book addresses the necessity of revised design guidelines that guarantee that play spaces are both accessible and inviting for all children, including those with disabilities, and that they support physical, emotional, and cognitive development. Vehicular movement and economic growth are frequently prioritised over the overall well-being of younger residents, walkability, and playability in contemporary planning principles. Consequently, the number of children's playgrounds, open spaces, and parks is frequently insufficient, and they are either inadequately maintained or situated in areas that are unsafe for children to access.This book also explores the vital transformation of Malaysia's urban spaces into environments that are genuinely child-friendly - an endeavour that demands strong political will and commitment from both local and federal governments. Central to this transformation is investment in sustainable practices and consistent maintenance, alongside the coordination of built environment facilities that not only comply with regulatory standards but also promote well-being, accessibility, and inclusivity. This includes facilities design for accessibility and inclusion and sustainable practice for inclusive facilities. additionally, the book underscores the critical importance of indoor air quality in safeguarding the health and well-being of children. Infrastructure development must be consistent with the UN Convention on the Rights of the Child (UNCRC), and participatory planning processes with children and carers must be made possible. In order to guarantee that every child can develop, play, and flourish in secure, nurturing environments that prioritise both interior and outdoor quality, it is imperative to promote government leadership, cross-agency collaboration, and sustained community engagement.This book functions as both a guide and a call to action, providing inspiration, strategies, and insights for the transformation of urban spaces into environments that prioritise the needs of children and uphold their rights in Malaysia and around the globe.